2022
DOI: 10.3389/fimmu.2022.1028850
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the vitamin D receptor expression during acute gastrointestinal graft versus host disease is associated with poor outcome after allogeneic stem cell transplantation

Abstract: The vitamin D receptor (VDR) is critical in regulating intestinal homeostasis and emerging evidence demonstrates that VDR deficiency is a critical factor in inflammatory bowel disease pathology. However, no clinical data exist regarding the intestinal expression of VDR in patients after allogeneic haematopoietic stem cell transplantation (HSCT). Analyzing intestinal biopsies from 90 patients undergoing HSCT with mortality follow-up, we demonstrated that patients with severe acute gastrointestinal graft versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Moreover, the expression of VDR expression in enterocytes and colonocytes within the gastrointestinal tract points toward the strong necessity of the VDR pathway to maintain gut epithelial integrity which is in line with previous findings. 30 Our findings suggest that CBD treatment significantly increased VDR expression in colorectal cell lines. Mechanism action of the potential antiinflammatory activity of CBD is likely mediated via the CB2 receptor.…”
Section: Effect Of Cbd On Mitochondrial Function -Atp Synthesismentioning
confidence: 54%
“…Moreover, the expression of VDR expression in enterocytes and colonocytes within the gastrointestinal tract points toward the strong necessity of the VDR pathway to maintain gut epithelial integrity which is in line with previous findings. 30 Our findings suggest that CBD treatment significantly increased VDR expression in colorectal cell lines. Mechanism action of the potential antiinflammatory activity of CBD is likely mediated via the CB2 receptor.…”
Section: Effect Of Cbd On Mitochondrial Function -Atp Synthesismentioning
confidence: 54%
“…Matos et al [35] have assessed intestinal biopsies in patients with severe GI-GvHD and found that there is a significant downregulation of VDR gene expression in these patients compared to those with mild or no GI-GvHD. The reduction of VDR expression was already detectable at the GI-GvHD onset compared to GvHD-free patients and correlated with antimicrobial peptide gene expression [35]. To summarize, all patients should take vitamin D supplements before and after undergoing allo-HCT.…”
Section: Before the Stormmentioning
confidence: 99%
“…117 Pretransplant vitamin D deficiency and the expression of the vitamin D receptor (VDR) were also associated with a higher risk of aGVHD. 118,119 Multiple interventional trials supplementing vitamin D before and after the transplant showed a general improvement in HSCT outcomes [120][121][122][123] with some differences according to the VDR genotypes. 124,125 The modulatory effect of vitamin D supplementation on the gut microbiota has been investigated in other medical conditions, showing a strong effect, particularly on the phyla Bacteroides and Firmicutes, as summarized in a recent systematic review.…”
Section: Non-prebiotic Nutrientsmentioning
confidence: 99%
“…Vitamin D HSCT outcomes improvements, [120][121][122][123] according to VDR genotype 124,125 Higher GVHD risk in vitamin D-deficient patients. 118,119 Vitamin D supplementation before and after the transplant reduces cGVHD incidence 123 NA Human studies, 118,120,125 not randomized clinical trials Meta-analysis of human studies 18 ; RCTs 153,154 18,153,154 Obesity Contrasting data: increased mortality and infections 15,21,27 ; no increased OS and infections [24][25][26]28 Contrasting data: increased risk of GVHD 15,27 ; no changes in GVHD risk 24,25 Reduction of microbial diversity; increased abundance of Akkermansia muciniphila and Enterococcus and reduction of Clostridiaceae family 22,23 Human 15,21,[24][25][26][27][28] and animal studies 22,23 15,21-28 aGVHD, acute graft-vs-host disease; aHSCT, allogeneic hematopoietic stem cell transplantation; EN, enteral nutrition; FOS, fructo-oligosaccharides; GFO, glutamine, fiber, and oligosaccharides; GOS, galacto-oligosaccharade; GVHD, graft-vs-host disease; HSCT, hematopoietic stem cell transplantation; NA, not available; OS, overall survival; PE-EVOO, polyphenolic extracts in extra virgin olive oil; PN, parenteral nutrition; RCT, randomized controlled trial; RS, resistant starch; SCFA, short-chain fatty acid; TMAO, trimethylamine-N-oxide; VDR, vitamin D receptor.…”
Section: Reduction Of Microbial Translocation and Pathogens 108mentioning
confidence: 99%